The Relationship of Fluid Restriction Compliance to Recurrence in Congestive Heart Failure Patients - Pipit Festi Wiliyanarti; Nadia Febriani; Septian Galuh Winata (PT. Griya Eka Sejahtera, 2022)
Background: Patients with congestive heart failure often experience recurrence and should be re-treated because of clinical syndromes. This study aimed to determine fluid restriction compliance on recurrence in patients with congestive heart failure.Methods: The research design used the analytic observational method. The research variables were fluid restriction compliance and the recurrence rate of patients with congestive heart failure. There were 40 patients as a sample of data which overall population of patients with congestive heart failure was in Dr. Soetomo Hospital by using the Consecutive Sampling technique. The data collection used a questionnaire.Results: The results showed that most respondents had high compliance (87.5%), the risk of recurrence was 26 patients (65%) by using the test result of Spearman Rho p=0,033.Conclusion: There is a relationship between fluid restriction compliance and the recurrence rate. Proper care and compliance for patients with congestive heart failure can reduce the risk of disease recurrence